The Role of CEO Power in Moderating Liquidity Risk and ESG Disclosure Effects on Firm Value - Baiq Vica Artamevia; Bambang Subroto; Sari Atmini (Postgraduate Program Merdeka University, 2024)
This study aims to examine the effect of liquidity risk and ESG (Environ-mental, Social, Governance) disclosure on firm value and to examine the role of CEO power in moderating the effect of liquidity risk and ESG disclosure on firm value. the research population is conventional banking listed on the Indo-nesia Stock Exchange in 2021-2023 totaling 43 companies. The sampling tech-nique used purposive sampling with a total research sample of 40 companies. The results of this study indicate that liquidity risk has no effect on firm value while ESG disclosure has a positive effect on firm value. the results also show that CEO power is unable to moderate the effect of liquidity risk and ESG dis-closure on firm value.DOI: https://doi.org/10.26905/afr.v7i2.13060